Synthesis and Characterization of TiO2 Nanotube Using Electrochemical Anodization Method - Khatun, Fatema; Azrina, Abd Aziz; A. K. M., Kafi; Sim, Lan Ching (Penerbit Universiti Malaysia Pahang, 2018)
In this study, Titaium dioxide (TiO2) nanotubes (TNTs) were synthesized by a simple electrochemical anodization method. TNTs were characterized by Field Emission Scanning Electron Microscope (FESEM), Transmission Electron Microscope (TEM), UV-Vis Diffuse Reflectance Spectra and Photoluminescence (PL) Spectra to identify the morphology, crystalline phase and photocatalytic activity under the visible light. . The morphological analyses revealed that the inner diameter, and tube length of the synthesized TNTs has an average value of 60 nm, and 900 nm, respectively. The wall thickness of the TNTs is of 11 nm. Theobserved TNTs have nanotubular shape. The absorption edge in the visible range at around 400-460 nm obtained from UV-Vis Diffuse Reflectance Spectrum analysis. In addition, the PL spectral peak identified at around 400nm and 590 nm. The finding shows thatthe synthesized TNTs made by electrochemical anodization method has photocatalytic properties and can be used as a photocatalyst for further photocatalytic application.